2018
DOI: 10.1007/s00221-018-5274-7
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual integration in depth: multisensory binding and gain as a function of distance

Abstract: The integration of information across sensory modalities is dependent on the spatiotemporal characteristics of the stimuli that are paired. Despite large variation in the distance over which events occur in our environment, relatively little is known regarding how stimulus-observer distance affects multisensory integration. Prior work has suggested that exteroceptive stimuli are integrated over larger temporal intervals in near relative to far space, and that larger multisensory facilitations are evident in fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 70 publications
0
18
1
Order By: Relevance
“…For instance, some investigators have used terms such as binding, integration, multi-modal advantage, etc. (e. g., Raij, Uutela, & Hari, 2000;Harrar, Harris, & Spence, 2017;Noel, Modi, Wallace, & Van der Stoep, 2018).…”
Section: Inmentioning
confidence: 99%
“…For instance, some investigators have used terms such as binding, integration, multi-modal advantage, etc. (e. g., Raij, Uutela, & Hari, 2000;Harrar, Harris, & Spence, 2017;Noel, Modi, Wallace, & Van der Stoep, 2018).…”
Section: Inmentioning
confidence: 99%
“…Likewise, other auditory or visuo-tactile integration studies ( Canzoneri et al, 2012 ; Kandula et al, 2015 ) have shown that RTs are shorter when a tactile stimulus is delivered at the impact time of the looming stimulus and suggest that looming stimuli predictively speed up tactile processing. Specifically, the speed of the looming stimulus seems to guide the nervous system in defining a high touch/impact probability window not unlike the multisensory temporal binding window described during the physiological and perceptual binding of two stimuli into the representation of a same and single external source and defining the degree of temporal tolerance of the brain in this binding process ( De Paepe et al, 2016 ; Noel et al, 2016 , 2018b ; for review, see Wallace and Stevenson, 2014 ).…”
Section: Looming Stimuli and Touch Or Impact Prediction To The Bodymentioning
confidence: 99%
“…However, different forms of sensory energy (i.e., light vs. sound) travel at distinct speeds and possess different neural transmission times. Hence, stimuli generated simultaneously from an environmental event may not be synchronous when they arrive at the peripheral organs (for example, due to distance; Van der Stoep et al ., ; Noel et al ., , in press), and these differences are likely to be propagated and amplified as the sensory information is processed in the brain. To account for these physical and neural differences, as well as the inherent noisiness involved in multisensory temporal coincidence detection, sensory information from the different modalities is integrated across a substantial temporal range—the temporal binding window (TBW; Dixon & Spitz, ; Lewkowicz, ; Munhall et al ., ; Diederich & Colonius, ; van Wassenhove et al ., ; Stevenson et al ., ; Wallace & Stevenson, ; Noel et al ., , ).…”
Section: Introductionmentioning
confidence: 99%